2015
DOI: 10.1016/j.cell.2015.05.051
|View full text |Cite
|
Sign up to set email alerts
|

A Conserved Circular Network of Coregulated Lipids Modulates Innate Immune Responses

Abstract: SummaryLipid composition affects the biophysical properties of membranes that provide a platform for receptor-mediated cellular signaling. To study the regulatory role of membrane lipid composition, we combined genetic perturbations of sphingolipid metabolism with the quantification of diverse steps in Toll-like receptor (TLR) signaling and mass spectrometry-based lipidomics. Membrane lipid composition was broadly affected by these perturbations, revealing a circular network of coregulated sphingolipids and gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
165
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 44 publications
8
165
0
Order By: Relevance
“…A negative regulatory role in innate immune signaling was uncovered in murine macrophages, where the enzyme is found on the cell surface and up-regulated upon inflammatory stimuli (11,12). Its knockdown results in enhanced responsiveness to Toll-like receptor (TLR) stimulation and Smpdl3b-deficient mice display an increased inflammatory response.…”
Section: Sphingomyelins (Sm)mentioning
confidence: 99%
“…A negative regulatory role in innate immune signaling was uncovered in murine macrophages, where the enzyme is found on the cell surface and up-regulated upon inflammatory stimuli (11,12). Its knockdown results in enhanced responsiveness to Toll-like receptor (TLR) stimulation and Smpdl3b-deficient mice display an increased inflammatory response.…”
Section: Sphingomyelins (Sm)mentioning
confidence: 99%
“…These lipids have a role in virtually all biological processes (van Meer, 2005) through their extensive, regulated association with other lipids and proteins. The significance of these regulatory circuits is evident from the variety of human disorders arising from altered protein-lipid interactions (Bayascas et al, 2008;Lindhurst et al, 2011;Zü chner et al, 2005;Kö berlin et al, 2015), which constitute attractive targets for pharmaceutical drug development (Hussein et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that membrane lipids are highly coregulated and revealed a conserved circular lipid network reflecting membrane lipid metabolism, subcellular localization, and adaptation mechanisms [8]. Network-wide functional annotation of lipids downstream of the Toll-like receptor signaling pathway based on genetic perturbations allowed accurate prediction of inflammatory responses in cells from patients with multiple lipidstorage disorders.…”
Section: Using Lipidomics To Unravel Pathways and Biomarkers In Metabmentioning
confidence: 98%